INNV-14. UTILIZATION OF A PATIENT FAMILY ADVISORY COUNCIL TO ADVANCE PATIENT-CENTERED CARE OF BRAIN TUMOR PATIENTS. (9th November 2020) - Pawloski, Jacob; Scarpace, Lisa; Gay, Nestelynn; Fadel, Hassan; Hunt, Rachel; Haider, Sameah; Robin, Adam; Snyder, James; Walbert, Tobias; Kalkanis, Steven; Lee, Ian
Abstract: INTRODUCTION: Developing and advancing patient-centered care within neuro-oncology is an essential element of any tertiary brain tumor center. Patient-centered care of neuro-oncology patients requires a holistic approach that integrates oncologic treatment with social and psychological support. OBJECTIVE: The aim of this study is to evaluate how a Patient Family Advisory Council can be created within an existing brain tumor center and utilized to improve patient-centered care. METHODS: Current patients and caregivers were recruited by brain tumor staff to participate in monthly meetings. All participants underwent screening and training by our Patient Education Research Center team. Discussions focused on current and future brain tumor center initiatives, and participants were encouraged to give feedback from the patient perspective. New ideas to improve the patient experience were solicited. RESULTS: A total of 15 participants (female = 57%) were recruited, including 10 with grade 3 or higher brain tumors. Monthly meetings, in-person or virtual, were held for two years. Utilizing participant feedback, the group updated our 80-page patient handbook that contained a variety of patient-caregiver focused resources. Participants also provided feedback on other brain tumor center initiatives such as development of a magnet featuring key phone numbers, an easily accessible website URL for emergencies, and numerous updates to the external website. Additional discussions involved development of neuro-oncology care pathways as we move to a stand-alone cancer center facility and initiation of OncoSTAT and palliative services in this population. CONCLUSION: Brain tumor patients require a comprehensive oncologic treatment team as well as a wide variety of support services. A Patient Family Advisory Council is an effective method of advancing patient-centered care and a step toward improving the neuro-oncology patient experience.